How to restore the Tropical Peat Swamp Forest in Aceh Province, Indonesia - Hairul Basri; . Sufardi; . Sugianto; Syamaun A. Ali; . Khairullah; Ahmad Reza Kasuri (Syiah Kuala University, 2015)
This study aims to describe the condition of Tripa Peat Swamp Forest (TPSF) in the Province of Aceh Indonesia that has been converted from forest to oil palm plantation and mixed farms. The results showed that the degradation of the peat soil and the environment have occurred in the TPSF. Degradation of peat is characterized by the occurrence of changes in water holding capacity and changes in chemical and physical properties of soil. Environmental degradation is characterized by changes in groundwater levels and land subsidence. TPSF restoration efforts can be carried out in accordance with the directives of land use and land conservation and water management